References of sexuality in relation to the Prophet Muhammad (Pbuh) in 17th-19th century selected French and English orientalist travelogues - Mohammad Rosli, Ummi Nadhirah; Omar, Noritah (Arab Society of English Language Studies, 2017)
This article examines references of sexuality in relation to Prophet Muhammad’s (peace be upon him)i within selected French and English 17-19th century Orientalist travelogues. It uses Edward Said’s theory of Orientalism to demonstrate how ‘sexuality’ as an attributed Western discourse about the Prophet (pbuh) developed into exotic ideas embodied in the image of the Arabs and Turks. The analysis explores three main leitmotifs that help shape the idea of the ‘Prophet’s sexuality’, namely the harem, slavery and the notion of the ‘Mohammaden Paradise’, all of which have implicit or direct referencing to the Prophet (pbuh). This article attempts to show how Orientalist travelogues in particular, have contributed to a very negative conception of Muhammad (pbuh) and his marital life—an image that unfortunately persists until today. The discourse carries with it a familiar yet dangerous binary attitude that continuously positions the West and Muslims antithetically. And in the centre of this narrative, the Prophet’s image gets convoluted by the predominance of the Western Orientalist discourse.